(untitled) (Journal of Social Sciences Review, 2023)
This study examined how aspiring educators describe technological pedagogical content knowledge, how its components relate to one another, and how far along the competency spectrum elementary school teachers are in their capacity to integrate technology into their classes. The 21st century has unified curricula, cutting-edge technologies, and comprehensive comprehension. To achieve educational excellence and student achievement in a rapidly modernizing society, teachers must learn new instructional methods and technologies. "Technological pedagogical and content knowledge" (TPACK) is a framework of collective and composite knowledge needed by teachers in technology-integrated classrooms. This study assessed pre-service teachers’ technology integration knowledge and behaviors. This cross-sectional survey assessed future educators’ TPACK and associated expertise. This survey uses questionnaire-based purposeful sampling. Surveys assessed technology, content, instructional techniques, and pedagogy. Each series of questions established a 5-point Likert scale, with 1 representing strongly disagreed and 5 representing strongly agreed. Smart PLS and SPSS analyzed data. Future educators are confident and able to use technology to fulfil student needs, according to the study. All three predictions were proven when all prospective educators surveyed understood TPACK. This shows that they understood the role of technology in each allegory or were confident in combining all three TK, PK, and CK structures. Findings determined implications.